Persepsi Ibu Postpartum yang Menyusui dalam Memenuhi Kebutuhan Nutrisi: Suatu Studi Ethnography pada Suku Jawa - Ratna Hidayati (Universitas Airlangga, 2016)
The perception that establish breastfeeding mothers in fulfilling the nutrition needson Javanese culture is derived from hereditary taught by their family and influential figures in the community. The purpose of this study is to know about the perception of Javanese breastfeeding postpartum mothers fulfilling nutritional needs. This is qualitative research with a principled approach to the study of the naturalistic inquiry. Information was obtained from 8 participants selected according tothe principle of sampling, those are the suitability and sufficiency which describe phenomena and linkages to research topics. Perception research results in fulfilling nutritional needs of breastfeeding mothers by adding the eating portion; forbid eating eggs and chicken. It is because they can cause wound inflammation/infection. Moreover, they try to increase their milk production by “wuwung bathing”, snacking the nuts and drinking “jamu gendongan”. All participants follow their parents’ suggestion, but high educated participants have the ability to negotiate with the parents. Nurses should have good interpersonal communication skills, understand the socio-cultural aspects and the uniqueness of the individual against the perception that is believed in order to avoid conflicts in changing perceptions related to nutrition, to develop and support the group including health personnel, family and clients.